Multiple certification uptake by coffee businesses: Evidence of functions and benefits from Central America - Donovan, Jason; Blare, Trent; Peña, Meliza (Wiley, 2020)
This article examines why and how nine coffee businesses in Central America engaged with multiple certification systems and the related functions and benefits. The businesses implemented, on average, four systems. Certification, in general, strengthened their negotiation position vis‐à‐vis exporters and international buyers, whereas multiple certification reduced the risks inherent in their reliance on any one certification, allowing businesses to sell as much coffee as possible at a relatively higher price. However, commitments to the certification's underlying goals were tenuous: Businesses engaged a subgroup of their supplier base in any one label, and coffee buyers purchased relatively small volumes of certified coffees, at times, conditioned on access to larger volumes of noncertified coffees. Although certification facilitated capacity upgrading, in many cases, the changes were minor and might have taken place without certification. Results suggest that multiple certification helps sustain small‐scale coffee exporters but dampen expectations that certification will drive long‐term systemic change in the sector. We conclude with recommendations for certification agencies and others that seek to support coffee businesses to expand their engagement in certified coffee markets.